Palm biomass downdraft gasification for producer gas production as renewable energy / Zulkifli Ab Rahman - Ab Rahman, Zulkifli (Institute of Graduate Studies, UiTM, 2012)
Biomass has been identified as a useful source material for many applications including the production of renewable energy after gasification of the biomass. The most promising future application of the thermal gasification of biomass will require a properly designed biomass gasification generating of tar free producer gas having trouble free operation of gasifier. In the current study, an experimental fixed-bed palm biomass gasification is utilized to investigate the gasification of empty fruit bunches using preheated air from 200oC to 400oC under autothermic conditions. The system consists of a gasifier and a gas cleaning system including cyclone separator, and venturi-wet scrubber.